Bahasa Inggris - Devanie Aulia Sherliantie; Margo Hadi Pura; Aryo Fadlian (Peneliti.net, 2022)
In Indonesia, crimes committed by minors occur frequently in various regions; it cannot be avoided despite the fact that various efforts have been made to stop criminal activities committed by minors, ranging from counseling in various critical places where children are educated to arresting children in trouble with the law and posting warnings in various locations throughout the city of Karawang, but many cases of children conflict with the law continue. The goal of this study is to discover how the regulations governing the criminal justice system for children in Karawang work. Using the normative juridical research method, it is possible to conclude: The presence of The Juvenile Criminal Justice System desires practical progress in the context of the best protection for children who are viewed as a valuable asset of a nation and country in the future, and whose rights must be protected Legal protection for children can be interpreted as an effort to protect laws that violate children's rights and various interests related to child welfare. Criminal liability clashed with minors with the laws through provisions regulated in the Criminal Code and Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. Criminal threats for children who commit an act against the law are determined by the Criminal Law, and the penalty for children who commit an act against the law is half of the maximum criminal threats from the Criminal Law on adults, while life imprisonment and capital punishment are not imposed on children who commit an act against the law.